2006
DOI: 10.1097/01.aco.0000192818.68730.9d
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the perioperative fluid management for the paediatric patient

Abstract: As free water excretion is altered for all children in the postoperative period, it is necessary to reduce the volume of maintenance fluid therapy to half the previously recommended volume. The choice of an isotonic solution should be more pertinent to that of a hypotonic solution, but evidence is lacking for a definitive answer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 50 publications
0
34
0
3
Order By: Relevance
“…This third space seems to start slowly redistributing around the third day after the surgery, contributing to the maintenance of a hypervolemic state. In addition, although these patients usually have a preserved renal function, the postoperative period is characterized by a rise in blood levels of antidiuretic hormone, 18 which promotes water retention and hemodilution and therefore delays the correction of the volemic status.…”
Section: Discussionmentioning
confidence: 99%
“…This third space seems to start slowly redistributing around the third day after the surgery, contributing to the maintenance of a hypervolemic state. In addition, although these patients usually have a preserved renal function, the postoperative period is characterized by a rise in blood levels of antidiuretic hormone, 18 which promotes water retention and hemodilution and therefore delays the correction of the volemic status.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia has been shown to be a negative prognostic indicator in children with traumatic brain injury, and is associated with reduced immune function and increased mortality in burn patients. 46 In a retrospective cohort study, early and prolonged hyperglycemia was found to be associated with a 3-and 6-fold increased risk of mortality, respectively, in critically ill children. 45 The incidence of hypoglycemia is not as common as previously thought, in an era where the amount of glucose administration has significantly decreased.…”
Section: Glucose During Maintenance Fluid Therapymentioning
confidence: 99%
“…Intraoperative glucose is no longer required in the maintenance fluid for the majority of children 1,19,30 The one group where there is uncertainty is the neonate.…”
Section: Should Maintenance Fluid Contain Glucose?mentioning
confidence: 99%
“…36 The worries concerning neonatal hypoglycaemia have tended to inform practice, so that glucose-containing solutions are used for maintenance in neonates, particularly when the neonate has an infusion of glucose or parenteral nutrition in the immediate preoperative period. 30 The normal glucose infusions used have concentrations ranging from 5% to 10%. These solutions may produce hyperglycaemia, which concern some.…”
Section: Should Maintenance Fluid Contain Glucose?mentioning
confidence: 99%